A ANÁLISE DO USO DA TERRA NO ENTORNO DO TRECHO OESTE DO RODOANEL MARIO COVAS NA CIDADE DE SÃO PAULO POR MEIO DE TÉCNICAS DE SENSORIAMENTO REMOTO - Volpe, Larissa Lucciane; Lombardo, Magda Adelaide (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
The construction of a highway may interfere with urban dynamics when transform  the land use around it. The western section of the road axles Mario Covas in the Metropolitan area of Sao Paulo in the neighborhoods of Perus and Jaragua in São Paulo city was studied with the characterization of the use and occupation of land around it. We did a survey of information with field work and were used remote sensing techniques for mapping. In a GIS have been made both types of digital classification, an analog and a automatic, a high resolution (IKONOS of 2002) and aerial photographs of 1994. For the comparative analysis showed that the classification analog was the most suitable for temporal analysis, because it allowed the preparation of thematic maps and better visualization of the results. With the quantitative analysis of the generate classes and worked, it was concluded, it was concluded that, in the year 1994 to 2002, the dense green area increased, the área of grass and scattered trees fell, the area of bare ground decreased, the built área increased. The results were organized in thematic maps showed the temporal analysis.